MANAJEMEN PELAKSANAAN PEMBERIAN BANTUAN KEUANGAN DAERAH DI PROVINSI KALIMANTAN TIMUR - Mirwan, Mirwan; Prakoso, Cathas Teguh; Daryono, Daryono (Tinta Nusantara 2018 Vol.1, 2025)
This study aims to describe and analyze the management of the implementation of East Kalimantan Governor Regulation Number 49 of 2020 concerning regional financial assistance, as well as to identify its supporting and inhibiting factors. Employing a qualitative descriptive approach. Data were collected through interviews, observations, and documentation, and analyzed using an interactive data analysis model. The research findings indicate that, in general, the management of regional financial assistance in East Kalimantan Province has been carried out in accordance with the normative framework of Governor Regulation Number 49 of 2020. However, its implementation faces various challenges in terms of communication, resources, disposition, and bureaucratic structure.